Architectural Membranes for improving the functional performance of buildings - Mendonça, Paulo (2019)
A well designed envelope separates the interior from the exterior so that the internal conditions are maintained with the minimum energy consumption. Due to its reduced weight, architectural membrane solutions may present some functional problems, namely acoustic and hygrothermal, when compared to conventional, heavier solutions. However, they also have potential and ecological advantages that can be exploited to enable the functional optimization of existing buildings in a sustainable way, due to the minimal use of material and the fact that they are dry assembling, easily reusable and recyclable solutions. This paper presents some emergent technologies for applying architectural membranes in building envelope, revealing ways to overcome the limitations for that they are recognized. Current trends include: hybrid membranes and coatings resulting from nanotechnology solutions; membranes with embedded smart technologies (batteries, LEDs, sensors), membranes incorporating Phase Change Materials and membranes for the purification and regulation of indoor air quality. Technological innovation in this field has advanced at an extraordinary pace in the last decades and has generated solutions that in some cases present functional performance equivalent to conventional solutions, but with less environmental impact.